Cross-Border Transactions in Higher Education: Philippine Competitiveness - Maria Andrea L. Santiago (Philippine Institute for Development Studies (PIDS), 2005)
The international education service sector is undoubtedly growing. The movement of students across nations is expected to grow fourfold in the next quarter of a century. Undaunted by the current domination by English-speaking providers, countries in Asia have taken big steps to be centers of education in the region, an ambition. Their single-mindedness in the pursuit of this vision has already made them countries to contend with. This paper shows that the focus and determination of countries like Singapore, Malaysia and China, is not present in the Philippine environment that is characterized by an unusually high dependence on the private sector to meet the growing demands for education. Marred by a highly politicized setting and inadequate resources, the education sector struggles in its aims to provide education for the growing population at an affordable rate and still maintain a decent level of quality. With these conditions, the Philippines, slowly losing its edge in English education in the region, can only hope to niche and attract foreign students and academics into specific programs and institutions, hopefully with the concerted support of government. If Government is serious in its desire to compete internationally, policymakers must address squarely the barriers to achieving this, including the enactment of laws to facilitate the influx of education services trade.
Keywords: 330; higher education; international education; cross-border transactions in education; trade in education services; foreign students; international degree costs; Dienstleistungshandel; Bildung; Bildungseinrichtung; Studium; Internationaler Wettbewerb; Philippinen